The Roles of Altruism, Free Riding, and Bandwagoning in Vaccination Decisions - Hershey, John C.; Asch, David A.; Thumasathit, Thi; Meszaros, Jacqueline; Waters, Victor V. (Organizational Behavior and Human Decision Processes, 1994)
Because vaccines can reduce the ability to transmit a contagious disease to others as well as the ability to contract a disease, the decision to vaccinate might be motivated in part by patients′ tendencies to act altruistically or, alternatively, to free ride on the vaccination decisions of others. We hypothesized that altruism and free riding motivate decisions to obtain vaccination, that individuals can be persuaded by the way questions are framed to free ride or to act altruistically, and that some individuals make vaccination decisions by "jumping on the bandwagon" and doing what most other people do. Four-hundred and seventy-two subjects answered whether they would agree to be vaccinated against a contagious disease under six different hypothetical scenarios. Regression analysis provides evidence that altruism (p < .001), free riding (p < .001), and bandwagoning (p < .001) are significant motivators in the decision to undergo vaccination. Frames stressing the opportunity to free ride increase free riding. Frames stressing altruism do not increase altruism. If generalizable to other settings, these results suggest that public health programs to increase vaccine usage should stress high vaccination rates.